Zagrożenia w działalności gospodarczej i ich pomiar - Mączyńska, Elżbieta (Threats in Business Activity and Their Measurement, 2005)
Global and local factors determining operation of companies and their surroundings may cause serious threats to business activity. It is possible to measure those factors and warn against bankruptcy mostly by employing models based on discriminant analysis. The paper shows such models created and verified based on data from Polish companies
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 245-257